The Post-War Anglo-American Far Right
XII, 155 p.
Keywords: Since 1945 neo-Nazi and far right extremists on both sides of the Atlantic have developed rich cultures which regularly exchange ideas. Leading activists such as Colin Jordan and George Lincoln Rockwell have helped to establish what has become a complex web of marginalised extremism. This book examines the history of this milieu to the present day.